MANAGEMENT OF ECTOPIC PREGNANCY: A TWO-YEAR STUDY - Mahboob, Urooj; Mazhar, Syeda Batool (Journal of Ayub Medical College Abbottabad, 2006)
Background: Ectopic pregnancy is the most important cause of maternal mortality and morbidity in the first trimester. Over the past few decades, the management of ectopic pregnancy has been revolutionized; various modalities of treatment are currently in practice. The purpose of this study was to determine the frequency of these modes of treatment of ectopic pregnancy and their outcome. Methods: Fifty two patients diagnosed to have ectopic pregnancy at MCH Center unit II in the year 2004 and 2005 were included in the study. A cross-sectional analytical study was done. Four modes of treatment were given according to patient’s condition, ultrasound findings and ÃŸ-hCG levels; these were laparotomy, operative laparoscopy, methotrexate injection and conservative management. The outcome measures included success of each treatment modality, need for second mode of treatment in each group and duration of hospital stay. Results: A total number of 52 patients with ectopic pregnancy were identified and studied. The rate of ectopic pregnancy was 1:100 deliveries. Emergency laparotomy was performed in 30 (57.9%) women, 15 (28.8%) received methotrexate injection. Seven women (13.3%) were managed conservatively and operative laparoscopy was not used as primary treatment in any of the patient. All cases of laparotomy did not require any further procedure. Twelve out of fifteen (80%) cases of medical treatment were successful while one (6.7%) proceeded to emergency laparotomy, one (6.7%) to operative laparoscopy and one (6.7%) to laparoscopy preceding laparotomy. Five out of seven patients (71.4%) on conservative treatment did not require any further intervention while two (28.6%) of them resolved with methotrexate injection. The duration of hospital stay in laparotomy, medically treated and conservatively managed groups was 6.5, 5.9 and 1.7 days respectively. Conclusion: In the institutional setting ectopic pregnancy accounted for 1% of total deliveries. More than half of all women with ectopic pregnancy presented with acute abdomen and required emergency laparotomy. About 40% women could be managed with non-surgical modalities with 80% success for methotrexate injection and 71% for conservative treatment in the present study. Keywords : Ectopic pregnancy, methotrexate, laparoscopy.